The development of design patterns inspired by the magroves species of Sungai Merbok / Nurul 'Ayn Ahmad Sayuti ...[et al.] - Ahmad Sayuti, Nurul 'Ayn; Azizan, Mohd Zamri; Ahmad Zamri, Ahmad Fazlan; Zainal @ Ismail, Mas Ayu; Ab Hamid, Abu Hanifa (Universiti Teknologi MARA, Kedah, 2018)
More than 30 species of mangroves have been identified in Sungai Merbok, Kedah alone NNW and it is considered to be largest collection of mangroves species in the world. Because of the profound natural and the historical elements, Sungai Merbok is now has been identified as a second natural biosphere in the world and is recognised by the UNESCO. The researchers found that the mangroves species have potentials to be developed into design patterns. The mangroves are the main inspiration and chosen to be further developed into product designs or any other form of designs (2D or 3D) such as textile products, graphic illustrations, fine arts, souvenirs, jewelleries and other fashionable items or home products. The original images of mangroves species were collected through research websites and books then were categorised in a typology matrix which are designed specifically for this study. The basic idea development on pattern of designs mangroves were also documented in the matrix. The variation on patterns shown different types of form of mangroves physical beings (such as roots, leaves, fruits, flowers, skin texture or other parts). It is estimated that 250 basic design patterns were developed from this study. However the design patterns are not yet finalised. Further developm will be done on the design develop is in the near future and will be the basis for more development of other design wor